Halogen light versus LED for bracket bonding: shear bond strength - Paulo Eduardo Guedes Carvalho; Valdemir Muzulon dos Santos; Hassan Isber; Flávio Augusto Cotrim-Ferreira (Dental Press Journal of Orthodontics, 2013)
INTRODUCTION: LED light-curing devices seek to provide a cold light activator which allows protocols of material polymerization with shorter duration. OBJECTIVE: The present study aimed to evaluate the shear bond strength of bracket bonding using three types of light-curing devices: One with halogen light (Optilight Plus - Gnatus) and two with LEDs (Optilight CL - Gnatus and Elipar Freelight - 3M/ESPE). RESULTS: Comparing the results by analysis of variance, the Gnatus LED device showed an inferior statistical behavior in relation to other light sources, when activated by a short time. But, when it was used for 40 seconds, the polymerization results were consistent with the other evaluated sources. The device with the best average performance was the halogen light, followed by the 3M/ESPE LED. CONCLUSION: It was concluded that the LEDs may be indicated in orthodontic practice, as long as a protocol is used for the application of light with the activation time of 40 seconds. INTRODUÇÃO: os aparelhos de fotopolimerização por LED buscam proporcionar uma luz ativadora fria, que possibilite protocolos de polimerização do material com menor tempo de duração. OBJETIVO: avaliar a resistência à tração da colagem de braquetes, utilizando três tipos de aparelhos fotoativadores: um de luz halógena (Optilight Plus - Gnatus) e outros dois de LED (Optilight CL - Gnatus; e Elipar Freelight - 3M/Espe). RESULTADOS: comparando os resultados por meio da análise de variância, o aparelho de LED Gnatus apresentou comportamento estatístico inferior em relação às outras fontes de luz, quando ativado por tempo reduzido. Já quando foi utilizado o tempo de 40 segundos, os resultados de polimerização foram compatíveis com as demais fontes avaliadas. O aparelho que apresentou melhor desempenho médio foi o de luz halógena, seguido pelo LED 3M/Espe. CONCLUSÃO: concluiu-se que os LEDs podem ser indicados na prática ortodôntica, uma vez que seja utilizado um protocolo de aplicação da luz com tempo de ativação de 40 segundos.